MARKER - a tool for building interactive applications for t-learning - Sousa, Sttiwe Washington Ferreira de; Bezerra, Ed Porto Bezerra; Soares, Ismênia Mangueira Soares; Brennand, Edna Gusmão de Góes (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
The growth of distance education has been enhanced by Massive Open Online Course and by the production of content broadcasted on television. The type of learning undertaken by Interactive Digital Television (iDTV) is also called Television-Learning (T- learning). Due to the possibilities of interactivity emerged with the creation of middleware Ginga, the T-Learning can cover a large number of learners. The marking video is a set of techniques used to insert additional interactive content in a video. As the development of applications for iDTV is still a costly process, because it requires a multidisciplinary team of developers to create tools for producing interactive applications for iDTV is a promising solution. The need for specific knowledge of technology or programming language should not be a prerequisite for this team. This paper presents a tool, called MARKER, for building interactive applications for iDTV whose main actors are the teacher (content creator) and student (interactive video user).